Desktop videoconferencing performance based on an ATM metropolitan area network. - Tobiet, H. (IEEE Communications magazine)
The DIVINE project enables us to evaluate a high-quality desktop videoconferencing system on an ATM network. After presentation of the methodologies and performance measurement tools used, we analyze the QoS of multimedia services implemented on the DIVINE system. Some performance evaluations have been achieved on the OASICE ATM MAN